Adaptive Resource Allocation Algorithm with Fairness for MIMO-OFDMA System - Jian Xu; Jongkyung Kim; Wonkyu Paik; Jong-Soo Seo (2006 IEEE 63rd Vehicular Technology Conference, 2006)
This paper investigates the subcarrier and power allocation problems of MIMO-OFDMA systems in order to maximize the total system capacity subject to the total power and proportional rate constraints of each user. We proposed an efficient resource allocation algorithm to determine the number of subcarriers for each user and then assign the subcarriers to each user. Simulation results show that the proposed resource allocation algorithm can make the capacity be distributed more fairly, very close to the ideal rate constraints, among users than the scheme which maximizes the system capacity only